Analisis strategi pengembangan koperasi terhadap kesejahteraan anggota - Rohmah, Itsnaini (Maliki Interdisciplinary Journal, 2024)
The era that continues to develop affects all areas of life, both social and economic. This influence can be positive or vice versa. The school cooperative is an organization that is in the school environment with members from the school itself. Its characteristic is that having a joint venture based on the principle of kinship with a democratic economic system can be an alternative to support solving socio-economic problems. His role as a teacher supporting the economy is very helpful for members in dealing with their daily economic problems. When viewed from the level of prosperity, basically it will be difficult for humans to get this achievement, because the need will continue to exist and increase. the aim of this research is to analyze the cooperative development strategy in order to achieve its main goal, namely the welfare of members. The method used in this study is qualitative research through data obtained from mini research and literature by collecting various literature. The results of this study explain that the strategy being implemented by the Paguyuban Al-Amanah Cooperative Madrasah Ibtidaiyah Negeri 1 Malang City is to improve the quality of cooperative institutions, add new business units to meet the needs of members, and improve services.